Skin diseases in patients with primary psychiatric conditions admitted in Psychiatry ward - Manish, Pradhan; Bijaya, Kaul; Dipa, Rai (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: The relation between psychiatric disorder and dermatological illness is well known but limited studies have been conducted to show significant association. This study was carried to find out the prevalence and frequency of dermatological illness in primary psychiatric patient. Material and Method: One hundred and fifty patients with primary psychiatric disease admitted in Nobel Medical College and Teaching Hospital from October 2017 to October 2018 with same number of age, sex and social class matched controls were studied. A detailed dermatological and psychiatric evaluation was done in all cases and controls. Results: The mean age for primary psychiatric illness was 30.94 ± 14.28 years. Dermatological conditions found in 82.67% of primary psychiatric condition was higher than that of controls (43.3%). The most common psychiatric condition was Schizophrenia (25.3%) followed by Depression (28%). A significantly higher incidence of infective dermatoses was seen in 65 (43.4%) of cases as compared to control 46 (30.6%) [p value = 0.023] in which dermatophytic infections was profoundly found in about 22 (14.7%) patients. Parasitic infestation was seen in 20% of psychiatric patients, of these scabies was present in 20 (13.3%) and pediculosis in 10 (6.7%) cases. Among non-infective skin disorder, high incidence of eczema 17 (11.3%) and generalized pruritus 15 (10%) was seen. Conclusion: There is a definite association of skin disease and primary psychiatric illness of which infective skin diseases are significantly higher in psychiatric patient. J Psychiatrists’ Association of Nepal Vol .6(1), 2017, p.48-53